Pengaruh Perilaku Keuangan dan Literasi Keuangan terhadap Keputusan Menabung Emas pada Nasabah PT. Pegadaian (Studi Kasus PT. Pegadaian Cabang Pangkalan Kerinci) - Gracia, Fransisca; Isni Andriana; Fida Muthia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of Financial Behavior and Financial Literacy on the Decision Customers to Saving Gold in PT. Pegadaian Pangkalan Kerinci. The sample in this study amounted to 98 customers using a purposive sampling technique. The data collection technique used a questionnaire. The data analysis technique used multiple linear regression analysis. The data was processed using te Statisfical for product and service solution (SPSS) program version 27. The results showed that financial behavior and financial literacy had a positive and significant effect on the decision customers to saving gold in PT. Pegadaian Pangkalan Kerinci.